Role of ethanol in the regulation of hepatic stellate cell Function - Wang, Jian-Hua (Baishideng Publishing Group Co., Limited, 2006)
Evidence has accumulated to suggest an important role of ethanol and/or its metabolites in the pathogenesis of alcohol-related liver disease. In this review, the fibrogenic effects of ethanol and its metabolites on hepatic stellate cells (HSCs) are discussed. In brief, ethanol interferes with retinoid metabolism and its signaling, induces the release of fibrogenic cytokines such as transforming growth factor β-1 (TGFβ-1) from HSCs, up-regulates the gene expression of collagen I and enhances type I collagen protein production by HSCs. Ethanol further perpetuates an activated HSC phenotype through extracellular matrix remodeling. The underlying pathophysiologic mechanisms by which ethanol exerts these pro-fibrogenic effects on HSCs are reviewed.